School Absenteeism During Menstruation Among Rural Adolescent Girls in Pune - Suman Bodat; Mrunalini M Ghate; Jyoti R Majumdar (Medsci Publications, 2013)
Background: Menstrual related problems and inadequate school sanitation facilities have an adverse effect on adolescent girl's academic performance and school attendance especially in rural setting. The following study was undertaken to determine school absenteeism during menstruation period. Objective: To assess the impact of menstruation on school attendance and factors affecting menstruation management. Methods: This cross sectional study was conducted in rural field practice area of Rural Heath Training Centre under Medical College, Pune among 740 adolescent girls in school by using pre-tested structured-questionnaires. Results: It was noticed that 269 (43.2%) girls used to remain absent from school during menstruation period. School absenteeism was significantly associated with menstrual disorders, socio economic status, material used during menstruation and abdominal pain during menstruation. Nearly 339 (54.5%) of rural girls bring pads/cloths to schools during menstruation while 283 (45.5%) do not bring pads/cloths to schools due to inadequate sanitation facilities. Conclusion: To prevent school absenteeism among these girls and intervention focusing on school menstrual management facilities and reproductive health education sessions is needed.